Spatial patterns in dissolved organic matter composition controlled by watershed characteristics in a coastal river network: The Neuse River Basin, USA. (1st February 2020) - Bhattacharya, Ruchi; Osburn, Christopher L.
Abstract: The effect of watershed characteristics (land use land cover and morphology) on spatial variability in dissolved organic matter (DOM) composition, and concentrations of dissolved organic carbon [DOC] and nitrogen [DON] was assessed in a coastal river basin draining into Pamlico Sound in eastern North Carolina, USA. Understanding the factors that influence DOM concentration and composition i.e., structurally complex molecules with high molecular weight versus low molecular weight, simple molecules can provide insights on DOM cycling and water composition implications. Such information is imperative for large coastal river networks undergoing rapid and intense land use and land cover (LULC) changes. DOM composition was estimated using optical indices calculated from DOM absorbance and fluorescence measurements. DOM was derived from terrestrial sources, and ordination analysis indicated that LULC, in particular, % wetland area was the most significant control on DOM composition and concentration. Wetland and agricultural coastal streams were abundant in humic and complex DOM, whereas forested and urban streams were least abundant in humic DOM. We speculate that greater availability of mobilizable DOM in wetland and agricultural watersheds contributed to this observation. In comparison, mixed urbanized and forested streams in North Carolina's Piedmont region were abundant in [DOC], less complex, low molecular weight DOM, as well as greater amounts [DON] due to higher urban runoff and elevated DOM production in these streams. Our results indicated that physiographic transition from Piedmont to coastal plain and varying LULC influenced the spatial variability in DOM composition and concentration. Our findings highlight that increasing anthropogenic alterations might increase the abundance of reactive DOM in coastal rivers and estuaries resulting in severe water quality issues. This information is important for monitoring and developing land use policies. Graphical abstract: Image 1 Highlights: DOM composition in a large river basin draining into an estuary was assessed. Basin-scale variability in DOM composition critical to assess ecosystem responses. DOM composition linked to prominent land use land cover and watershed characteristics. DOM optical indices are easy monitoring tool to assess C cycling in coastal systems.